Non-cooperative 4E-BP2 folding with exchange between eIF4E-binding and binding-incompatible states tunes cap-dependent translation inhibition - Jennifer E. Dawson (Nature Portfolio, 2020)
Phosphorylation of eIF4E binding proteins (4E-BPs) controls their folding and regulates cap-dependent translation. Here, the authors show that phosphorylation of the C-terminal disordered region stabilizes the non-cooperatively folded 4E-BP domain to an eIF4E binding-incompatible state to control translation.